Socio-hydrological dynamics and water conflicts in the upper Huasco valley, Chile - Dame, Juliane; Nüsser, Marcus; Schmidt, Susanne; Zang, Carina (Frontiers in Water, 2023)
In arid regions of north-central Chile, mining activities and agricultural land use changes lead to competing water demands, water insecurity, and related conflicts. Different actors across the region, including mining companies, agricultural producers, and local communities rely on scarce water resources, which are highly dependent on the Andean cryosphere. Based on an integrated perspective on human-water-relations, this study investigates changing water demands and conflicts in the upper Huasco valley that faces adverse environmental impacts and conflicts over mining activities and export-oriented agriculture. This article contextualises land use changes, water governance, and the precarious drinking water situation from a socio-hydrological perspective using social science and remote sensing methods. Results from remote sensing analyses show a drastic glacier decrease in the vicinity of the mining project, where three glaciers completely disappeared since 2000. Furthermore, an expansion of the cultivated area from 2,000 ha in the 1990s to about 3,210 ha occurred in the 2000s. Agricultural expansion has come to a halt and only a slight increase of 100 ha can be detected over the last decade. Interview and social media data show local concerns and discourses on issues of water scarcity and quality related to these dynamics of land use change. The study stresses the necessity of integrative socio-hydrological assessments for a better understanding of water related conflicts and as a base for equitable water governance in climate-sensitive and conflict-prone areas.